ANALISIS LAPORAN KEUANGAN UNTUK MENILAI KESEHATAN KEUANGAN PADA KSP TANI MAKMUR DI KASIHAN BANTUL - Luluk Fuatimah; Ratih Kusumawardhani (FE Program Studi Manajemen, 2022)
This study aims to assess and analyze the health level of the Tani Makmur Savings and Loan Cooperative (KSP) in 2013-2018 based on the Regulation of the Deputy for Supervision of the Ministry of Cooperatives and SMEs Number: 06 / Per / Dep.6 / IV / 2016. This research is quantitative descriptive. The research subject is the Tani Makmur Savings and Loan Cooperative (KSP) and the object of the research is the level of health. Collecting data in research using interview and documentation methods. The data analysis technique used is the ratio analysis technique. The results of this study indicate that the overall health level of KSP Tani Makmur in 2013-2018 is in the category under supervision, getting a mean score of 62.73. The capital aspect gets a score of 31.33 (Under Special Supervision); aspects of the quality of earning assets get a score of 61.00 (Under Supervision); management aspects get a score of 98.00 (Healthy); efficiency aspects get a score of 68.30 (Fairly Healthy); the liquidity aspect gets a score of 50.00 (Under Special Supervision); aspects of independence and cooperative growth get a score of 37.50 (Under Special Supervision); as well as aspects of cooperative identity get a score of 100.00 (Healthy).